Design of an Information System for Testing the Blood Characteristics on Increasing the Impact of Vibration using a Prototype “Blood Shaker Machine” - Jessica Juan Pramudita; Edy Susanto; Luthfi Rusyadi (Inspirasi Foundation, 2022)
Objective: The general purpose of this research is to design an information system based on the application of blood characteristics testing on platelets to increase the impact of vibration by using a